Acrylamide determination in Portuguese food matrices by UPLC-PDA and UPLC-MS - André, Catarina (2016)
The aim of this study was the determination of acrylamide in Portuguese food matrices thought the development and optimization of a chromatographic method with two different detectors. Acrylamide is classified by the International Agency for Research on Cancer (IARC) as a probable carcinogenic compound and the growing concern in human food is due to the fact that it was found in some foods when processed at high temperatures. Samples were bought randomly in local supermarkets and correspond to foods that suspect to contain high levels of this compound and contribute significantly to human consumption such as bolo do caco, fries, breakfast cereals, biscuits, coffee, coffee substitutes and pastel de nata. Sample preparation involved solid phase extraction. To quantify acrylamide were developed two chromatographic methods, UPLC-PDA and UPLC-MS/MS. The method who proved to be more suitable and quantify unequivocally acrylamide was UPLC-MS/MS. The chosen foodstuff for acrylamide determination presented a dissimilar range of values. Bolo do caco values depends on the cocking procedures. The lowest cooking temperature yield a lower acrylamide content (669 µg/Kg) while with the two samples cooked with the highest temperature the acrylamide content was must higher (1653 µg/Kg). In fries the content of acrylamide found was approximately 365 µg/Kg, while for breakfast cereals it varies between 238 and 187 µg/Kg depending on chocolate content. The content found was 58 µg/Kg for crackers and 203 µg/Kg for gingerbread. Coffee substitutes presented a value 5 times more than the coffee which was the lowest value determined with an acrylamide value of 25 µg/Kg. According to EFSA acrylamide values for pastry are between 75 and 1044 µg/Kg and the content of pastel de nata was 331 µg/Kg. The acrylamide content in all samples of Portuguese products analyzed were below the indicative values published by EFSA and are not considered to be main hazards of concern.